Impact of Greenwashing, Subjective Norm, and Perceived Behavioral Control on Purchase Intention for Eco-Friendly Packaged Fast-Moving Consumer Goods: The Mediating Role of Green Trust - Khoiriah, Rizka Ismi; Imaningsih, Erna Sofriana (International Journal of Social and Management Studies, 2025)
The rising public awareness of environmental issues has influenced consumer behavior, particularly in purchasing environmentally friendly products. This study analyzes the influence of Greenwashing, Subjective Norm, and Perceived Behavioral Control on Green Purchase Intention for eco-friendly packaged Fast Moving Consumer Goods (FMCG), with Green Trust as a mediating variable. A total of 250 respondents from Banten, Jakarta, and West Java, who are knowledgeable about environmental issues and eco-friendly FMCG products, were selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. Results indicate that Subjective Norm and Perceived Behavioral Control have a significant positive effect on Green Trust. Additionally, Subjective Norm, Perceived Behavioral Control, and Green Trust significantly influence Green Purchase Intention. While Greenwashing does not significantly affect Green Trust, it has a significant negative effect on Green Purchase Intention. Mediation analysis shows that Green Trust does not mediate the relationship between Greenwashing and Green Purchase Intention, but partially mediates the relationships between Subjective Norm and Perceived Behavioral Control with Green Purchase Intention. These findings offer important theoretical and practical insights into consumer behavior toward environmentally friendly packaged products.